'The Heart of Europe': The Origins and Fate of a Czech Nationalist Cliché. (1st May 2013) - Pynsent, Robert B
Abstract : This article considers the Czech cliché 'the heart of Europe' and its sentimentalization. It ends by linking the Czech heart with another nationalist symbol, the heart-leaved linden. The article derives the nationalist symbolism of the heart from medieval Saxon mysticism and its descendants, the Baroque cult of the Sacred Heart, taking in Cupid and his arrows on the way. Sources from the seventeenth to the twentieth century include belles-lettres, but also political writing from the Romantic historian Palacký to Václav Havel.